Depression and termination of pregnancy (induced abortion) in a national cohort of young Australian women: the confounding effect of women's experience of violence - Watson Lyndsey F; Taft Angela J (BMC, 2008)
Abstract Background Termination of pregnancy is a common and safe medical procedure in countries where it is legal. One in four Australian women terminates a pregnancy, most often when young. There is inconclusive evidence about whether pregnancy termination affects women's rates of depression. There is evidence of a strong association between partner violence and depression. Our objective was to examine the associations with depression of women's experience of violence, pregnancy termination, births and socio-demographic characteristics, among a population-based sample of young Australian women. Methods The data from the Younger cohort of the Australian Longitudinal Study on Women's Health comprised 14,776 women aged 18-23 in Survey I (1996) of whom 9683 aged 22-27 also responded to Survey 2 (2000). With linked data, we distinguished terminations, violence and depression reported before and after 1996. We used logistic regression to examine the association of depression (CES-D 10) as both a dichotomous and linear measure in 2000 with pregnancy termination, numbers of births and with violence separately and then in mutually adjusted models with sociodemographic variables. Results 30% of young women were depressed. Eleven percent (n = 1076) reported a termination by 2000. A first termination before 1996 and between 1996 and 2000 were both associated with depression in a univariate model (OR 1.37, 95%CI 1.12 to 1.66; OR 1.52, 95%CI 1.24 to 1.87). However, after adjustment for violence, numbers of births and sociodemographic variables (OR 1.22, 95%CI 0.99 to 1.51) this became only marginally significant, a similar association with having two or more births (1.26, 95%CI. 1.00 to 1.58). In contrast, any form of violence but especially that of partner violence in 1996 or 2000, was significantly associated with depression: in univariate (OR 2.31, 95%CI 1.97 to 2.70 or 2.45, 95% CI 1.99 to 3.04) and multivariate models (AOR 2.06, 95%CI 1.74 to 2.43 or 2.12, 95%CI 1.69 to 2.65). Linear regression showed a four fold greater effect of violence than termination or births. Conclusion Violence, especially partner violence, makes a significantly greater contribution to women's depression compared with pregnancy termination or births. Any strategy to reduce the burden of women's depression should include prevention or reduction of violence against women and strengthening women's sexual and reproductive health to ensure that pregnancies are planned and wanted.